The Effectiveness of Feeding Maggots (Hermetia illucens) and Aurantiochytrium Microalgae Biomass on the Productivity of Sangkuriang Catfish (Clarias sp) - Meitiyani Meitiyani; Andri Hutari; Dhanty Cynthia Prameswari; Putri ayu Ridhaillahi (Jurnal Biologi Tropis, 2023)
Maggot or fly larva black soldier fly (Hermetically illucens) has been widely reported to be able to improve the growth performance of farmed fish because it contains high protein. Adding microalgae Aurantiochytrium sp. which contains omega-3 docosahexanoic acid (DHA) enriches the quality of fish feed. This research used a Completely Randomized Design (CRD) consisting of six treatments, each consisting of four repetitions with the percentage of maggot and microalgae. Aurantiochytrium sp. different ones. Then the ANOVA test was continued after fulfilling the requirements for normality and homogeneity of the data, then the Least Significant Difference (BNT) Follow-up Test was carried out. All parameters of absolute weight, relative weight, absolute length, relative length have value F>F table. The optimum animal feed formulation resulting from this research was obtained in P3 treatment with a composition of Corn Flour + Bran 59%, Maggot 30%, Aurantiochytrium,sp 11%. Providing variations in maggot composition black soldier fly (Hermetically shining) and micro algae Aurantiochytrium sp affects the growth of catfish (Clarias, Sp.). It is hoped that the results of this research will become fish animal feed that produces protein and omega 3 DHA content in fish as a source of quality animal protein for humans.